2003
DOI: 10.1023/b:jobb.0000008026.37790.5a
|View full text |Cite
|
Sign up to set email alerts
|

  Subunits of Voltage-Gated Calcium Channels

Abstract: Calcium channel beta subunits have marked effects on the trafficking and on several of the biophysical properties of all high voltage activated calcium channels. In this article I shall review information on the different genes, on the structure of the beta subunits, and on their differential expression and post-translational modification. Their role in trafficking and assembly of the calcium channel heteromultimer will be described, and I will then review their effects on voltage-dependent and kinetic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
376
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(396 citation statements)
references
References 168 publications
(289 reference statements)
13
376
1
6
Order By: Relevance
“…So, how does the lack of the ␤ 1a protein affect expression and function of the DHPR in skeletal muscle? Based on extensive coexpression experiments in heterologous systems (31,32) and on results from the ␤ 1a -null mouse (8,11), a lack of ␣ 1S triad expression would have been expected. However, immunofluorescence analysis of the fully differentiated zebrafish myotubes clearly demonstrated that ␤ 1a deficient cells are able to correctly target ␣ 1S into the triads (Fig.…”
Section: ) Statistical Significance Was Determined By Using the ⌬Cmentioning
confidence: 99%
“…So, how does the lack of the ␤ 1a protein affect expression and function of the DHPR in skeletal muscle? Based on extensive coexpression experiments in heterologous systems (31,32) and on results from the ␤ 1a -null mouse (8,11), a lack of ␣ 1S triad expression would have been expected. However, immunofluorescence analysis of the fully differentiated zebrafish myotubes clearly demonstrated that ␤ 1a deficient cells are able to correctly target ␣ 1S into the triads (Fig.…”
Section: ) Statistical Significance Was Determined By Using the ⌬Cmentioning
confidence: 99%
“…To direct the signal to a specific subset of an extensive family of effectors, cells are endowed with a complex network of regulators that constrain the timing and spreading of the calcium increase. The subset of voltage-dependent calcium channels that are activated by strong depolarization, also called high voltage-activated (HVA) 3 channels, are heteromultimers consisting of a central pore-forming subunit (Ca V ␣ 1 ) that associates with one or more accessory subunits. Among them the accessory ␤-subunit (Ca V ␤) has traditionally been recognized as one of the most important modulator of HVA channels (1)(2)(3).…”
mentioning
confidence: 99%
“…The subset of voltage-dependent calcium channels that are activated by strong depolarization, also called high voltage-activated (HVA) 3 channels, are heteromultimers consisting of a central pore-forming subunit (Ca V ␣ 1 ) that associates with one or more accessory subunits. Among them the accessory ␤-subunit (Ca V ␤) has traditionally been recognized as one of the most important modulator of HVA channels (1)(2)(3). More recently, it has been shown that the same subunit mediates several other cellular processes (for review, see Ref.…”
mentioning
confidence: 99%
“…Divergence of ␤ subunit sequences has permitted multiple modulatory functions of ␤ subunits, which act in a cell type and calcium channel-specific manner (6,7). However, the virtual structural invariance of the ␤ subunit core across divergent species and its resemblance to a membrane-associated guanylate kinase scaffolding molecule suggests that a primary role of the ␤ subunit may be to stabilize membrane protein complexes associated with high voltage-activated calcium channels.…”
Section: Lymnaea Neurons Express a Ca V ␤ Subunit-a Full-lengthmentioning
confidence: 99%
“…Like other types of high voltage-activated channels, Ca v 2 channels exist as macromolecular complexes of a pore-forming ␣ 1 subunit and ancillary ␤, ␣ 2 -␦, and possibly ␥ subunits (5). The mammalian brain expresses four different types of ␤ subunits that interact to differentially modulate ␣ 1 subunit function (6,7). The functional effects of ␤ subunit coexpression include changes in the voltage dependences and rates of activation and inactivation, plus an increase in current densities (8 -17).…”
mentioning
confidence: 99%